An alternate form of probability-distribution plot for De values - Berger, G. W. (Ancient TL, 2010)
The use of probability density distribution (PDD or PD herein) plots for summarizing visually the distributions of paleodose (De) values (even when accompanied by a displayed ranking of De values) has been criticized over the past decade. Here the suitability of this plot is revisited and an alternate form is proposed for creating a more realistic statistical representation of such data. The alternate plot (TPD, Transformed-PD) is generated by use of a logarithmic transform of De values and use of relative, rather than absolute, errors in De values. The radial plot also employs such parametric transforms. Examples are given and discussed of distributions of De values from both multiple-grain and single-grain SAR (Single Aliquot Regenerative dose) experiments for which a youngest-age interpretation is required. The PD and TPD representations of these data are compared with each other and with the corresponding radial plots. These examples illustrate both the systematic advantages of the TPD plot compared to the conventional PD plot (as heretofore used with De data sets) and some limitations of the TPD plot. These limitations can be viewed as either minor or major, depending upon the data set. Generally, the use of the TPD plot (together with ranked De values) is an improvement over the comparable use of the PD plot.